Clinical effectiveness of Finger gliding Exercise for patients with trigger fingers receiving steroid injection: a Randomized Clinical Trial - Yue Kwan Choi; Regina Wing-Shan Sit; Bo Wang; Christina Cheuk; Man Kei Lee; Kwan Wa Maria Leung (Scientific Reports, 2025)
Abstract Finger gliding exercises are believed to enhance flexor tendons excursion. This study assesses the effectiveness of finger gliding exercises in patients after receiving steroid injections for trigger fingers. Patients with trigger fingers who received corticosteroid injection were randomly assigned (1:1) to control and intervention group. The intervention group was required to do finger exercises and submit online exercise log regularly. The clinical outcomes of trigger fingers at 24 weeks and compliance with finger gliding exercises were assessed via online surveys. A total of 38 participants were allocated to each group. Baseline characteristics were similar, except for a longer duration of symptoms in the intervention group (5.2 ± 2.9 vs. 3.6 ± 2.6 months, P = 0.002). At 24 weeks, 34 (89.5%) control and 33 (86.8%) intervention group participants responded to online survey. No statistical significant differences were observed in Numerical Pain Rating Score, Quinelle grading, finger improvement rate, recurrence of triggering, need for repeated injection and occurrence of new trigger finger sites. The exercise log response rate and compliance rate were 85.6% and 68.6%. In conclusion, our study did not establish the clinical effectiveness of finger gliding exercise for trigger finger patients following steroid injections compared to usual care.